1997
DOI: 10.1038/sj.bmt.1700831
|View full text |Cite
|
Sign up to set email alerts
|

Additional immunotherapy on the basis of increasing mixed hematopoietic chimerism after allogeneic BMT in children with acute leukemia: is there an option to prevent relapse?

Abstract: Summary:Case reports Patient No. 1 The success of allogeneic BMT (allo-BMT) in children with acute leukemias is mainly affected by relapse.The first patient, a 2-year-old boy with MDS (CMML and There is evidence that these patients have only a little monosomy 7), was referred for BMT. After conditioning or no benefit from additional immunotherapy if the with busulfan (BU) 20 mg/kg, etoposide (VP16) 40 mg/kg treatment is started in frank hematological relapse.and cyclophosphamide (CY) 120 mg/kg, the patient was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 0 publications
0
33
0
1
Order By: Relevance
“…From the data presented in this study, additional immunotherapy -ie tapering of immunosuppression followed by DLI, if needed, may be given when MC is detected in the leukemiaaffected cell lineage in PB Ͼ1 month after SCT. Bader et al 6,57 have also reported promising results using this approach. However, more data from different laboratories are needed to evaluate the impact of MC in BM and also in PB before any definite treatment recommendations can be made.…”
Section: Discussionmentioning
confidence: 85%
“…From the data presented in this study, additional immunotherapy -ie tapering of immunosuppression followed by DLI, if needed, may be given when MC is detected in the leukemiaaffected cell lineage in PB Ͼ1 month after SCT. Bader et al 6,57 have also reported promising results using this approach. However, more data from different laboratories are needed to evaluate the impact of MC in BM and also in PB before any definite treatment recommendations can be made.…”
Section: Discussionmentioning
confidence: 85%
“…6,8,9,[33][34][35] Although persistent recipient cells are not necessarily associated with an increased relapse rate, 36 several reports have shown, that the incidence of recurrent disease is significantly increased in the group of patients with unstable mixed chimerism showing increasing host signals compared to patients presenting with stable complete chimerism or patients with mixed chimerism turning into complete chimeras. 24 In this situation it is of critical importance to have a quantitative method for the evaluation of chimerism to provide useful information which could serve as a basis for clinical decision making.…”
Section: Discussionmentioning
confidence: 99%
“…4 Thus, careful monitoring of the dynamics of chimerism has become especially important to schedule therapeutic intervention. [5][6][7][8][9] In sex-mismatched transplantation, FISH analysis of X and Y chromosomes can easily be performed to quantify donor and recipient hematopoiesis. [10][11][12][13][14] Established procedures are commercially available, thus making standardization of the methods possible and ensuring comparable results.…”
Section: Introductionmentioning
confidence: 99%
“…These patients are then referred to have an 'increasing' or an 'decreasing mixed chimerism'. 14,16,17 Peripheral blood or bone marrow is most often used for chimerism analysis with or without further manipulation of different cell subpopulations. It is important to realize that patients could show complete chimerism in one compartment, for example, NK cells, whereas others could be totally or in part recipient derived.…”
Section: Tionmentioning
confidence: 99%